L’évolution récente de l’utilisation du sol sur la rive nord du Saint-Laurent entre Québec et Montréal - Clibbon, Peter; Gagnon, Jacques (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1965)
In recent years, the face of much of rural Québec bas undergone a series of important transformations : vast areas of marginal farmland have either been abandoned or reforested ; large tracts of cleared land in the Saint Lawrence lowlands have been converted from general farming to specialty crops ; several of these areas of specialty crops are now being swallowed up by urban expansion ; the Laurentide hills and large sections of the Eastern Townships area are rapidly being transformed into sprawling tourist playgrounds. With the aid of 1964 air photos and 1965 land use data the authors record and briefly discuss some of the more striking trends in the evolution of rural land use patterns in the area between Montréal and Québec City, on the north shore of the Saint Lawrence River.